2020
DOI: 10.1186/s12915-020-00834-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the suppression of a malaria vector using a CRISPR-Cas9 gene drive to reduce female fertility

Abstract: Background: Gene drives based on CRISPR-Cas9 technology are increasingly being considered as tools for reducing the capacity of mosquito populations to transmit malaria, and one of the most promising options is driving endonuclease genes that reduce the fertility of female mosquitoes. In particular, there is much interest in constructs that target the conserved mosquito doublesex (dsx) gene such that the emergence of functional driveresistant alleles is unlikely. Proof of principle that these constructs can le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 42 publications
5
118
0
Order By: Relevance
“…Outcomes consistent with chasing behaviour have already been observed in other models of suppression gene drives in structured populations (Bull et al, 2019; North et al, 2019, 2020). In these studies, it was suggested that the drive efficiency should be high enough to avoid stochastic drive loss but should not be so high that the drive eliminates patches of wild‐type alleles and itself before being able to spread to an adjacent region.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Outcomes consistent with chasing behaviour have already been observed in other models of suppression gene drives in structured populations (Bull et al, 2019; North et al, 2019, 2020). In these studies, it was suggested that the drive efficiency should be high enough to avoid stochastic drive loss but should not be so high that the drive eliminates patches of wild‐type alleles and itself before being able to spread to an adjacent region.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we systematically explore how a population model that explicitly incorporates continuous space affects the dynamics and outcome of a suppression gene drive release. We show that a dynamic phenomenon we term “chasing,” which is similar to the pattern of local eradication followed by recolonization observed in previous studies (Bull et al, 2019; North et al, 2019, 2020), can lead to long‐term, unstable coexistence between drive and wild‐type alleles. We analyse the propensity of different types of suppression drives to produce such chasing dynamics and show how this phenomenon depends on the ecological and demographic parameters of the population.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast with the other two drives, the Y-shredder is not a homing drive (though homing sex-chromosome shredder drives have been proposed and constructed 47,6668 ). The drive is located on the X-chromosome and shreds the Y-chromosome in germline cells.…”
Section: Methodsmentioning
confidence: 99%